At first reading: whether it changes, how it changes and whether it can further change the “end of life” in Italy after sentence 135 of 2024 (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The essay (at first reading) analyses the scope and novelties introduced in Italy on the subject of end-of-life following the recent constitutional ruling No 135/2024.
Keywords: End of life; assisted suicide; life-support treatment; euthanasia; constitutional jurisprudence